The institution of industrial education: a platform for trade learning and skill sharing- connecting spatial and social divisions through light- duty education in Wynberg - Benington, Blue Arizona (My University, 2022)
I want to propose an educational institution for the construction and trade industry. A place focused on skills-based learning as a type of partnership for individuals throughout their careers. A place for artisanal craftsmanship as well as a technical advisor for small scale companies in the construction industry. The idea is that the institution becomes a platform, a decentralized economy of micro-businesses and tradespeople interconnected and accessible to one another and the greater public. The institution becomes a continuum of the construction industry, a place for real-life learning and advisory. Providing access to a pool of diverse skills and knowledge base for people to bridge and progress through different facets of the economy. The idea is that the center is a place for skills development through practical training and on the other a place for greater public communication through providing a place for diverse economic interaction and skill sharing. The centre is a communal space, a node of the city and a corridor that forms a bridge between the community, industry and the greater economy
A research report submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Architecture (Professional)